Impact of different treatments of balanced fertilization and foliar spray on growth and yield for two apple cultivars trees Royal gala", "Granny smith" and the rootstock Malus sylvestris (L.) Mill and also alleviation Eriosoma lanigerum (Hausmann) infestation - ديوب, سمر; رشيد خربوتلي; نبيل أبو كف (Latakia University Journal -Biological Sciences Series, 2025)
The experiment was carried out during seasons of 2020 and 2021 in Kassab village on two apple cultivars "Royal gala", "Granny smith" and the rootstock Malus sylvestris (L.) Mill fifteen years old and grafted on M. sylvestris .The aim of this study to know the effect of balanced fertilization with the foliar sprays. To study its effects we apply four treatments (control, fertilizer, fertilizer + foliar sprays once, fertilizer + foliar sprays twice). Then estimated the length of recent growth and calculated the percentage of fruit setting and also the production amount (Kg/ tree), the percentage of aerial or vegetative infestation by woolly apple aphid (AI%) were calculated. The results had showed in both seasons that the fertilization treatments reduced remarkably the percentage of aerial infestation (AI %) and improved the percentage of fruit setting and increased apple productivity in compared to control treatment in all tested cultivars and rootstocks. The lower percentage of aerial infestation (AI%) were in the fourth treatment (fertilizer + foliar sprays twice) for "Royal gala", "Granny smith", But the lower percentage of aerial infestation (AI%) for M. sylvestris in the treatment (fertilizer + foliar sprays once). As a result of the statistical analysis of percentage of Aerial infestation (AI%), there were differences between all the studied treatments with the superiority of fourth treatments (fertilizer + foliar sprays twice) in Cultivars "Royal gala" and "Granny smith". The lower percentage of aerial infestation (AI %) were 11.50 % as the average of the two seasons compared to control 35.08 % for " Royal gala" and also the highest length of recent growth length were 74.25 cm compared to control treatment 62.59 cm as the average of the two seasons in the fourth treatment in the " Granny smith" trees.